TPACK-based hybrid learning model design for computational thinking skills achievement in mathematics - Helsa, Yullys; Turmudi; Juandi, Dadang (Journal on Mathematics Education, 2023)
Hybrid learning implementation is closely related with technology. In designing hybrid lessons, lecturers need to have both the pedagogical and content-related skills that make the best use of technology so that it also improves the students’ skills, including their computational thinking skills. The purpose of this research is to examine whether a hybrid learning model based on Technology Pedagogy and Content Knowledge (TPACK) affects the computational thinking skills achievement in a valid, practical, and effective manner. This research is development research using the Plomp’s model and is described in a qualitative descriptive manner. The participants were lecturers and 38 first-year students at Primary School Teacher Education Study Program of Padang State University. The instruments were validation sheets, practicality assessment sheets by lecturers, questionnaire sheets for students, and computational thinking skills test questions. The results of the validity test show that in terms of content, language, and e-learning practice, they all met very valid criteria with an average percentage score of 85.9%, 86.2%, and 84.1%, respectively. The practicality test results of model handbooks, Semester Lesson Plans, Lecture Program Units, computational thinking questions, additional material, and e-learning model meet the practical criteria with an average percentage score of 77.5%, 86.8%, 89.1%, 83.8%, 79%, and 82.4%, respectively. The average percentage of student assessment scores is 82.9% and meets the practical criteria. The results of the effectiveness test showed that 21.9% of students had reached the moderate level, 6.3% reached the low level, and 71.9% reached the very low level. This study recommends future researchers to develop a hybrid learning model based on TPACK to achieve other 21st-century abilities.